2018
DOI: 10.1038/s41598-018-24459-z
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired photosynthesis and increased leaf construction costs may induce floral stress during episodes of global warming over macroevolutionary timescales

Abstract: Global warming events have coincided with turnover of plant species at intervals in Earth history. As mean global temperatures rise, the number, frequency and duration of heat-waves will increase. Ginkgo biloba was grown under controlled climatic conditions at two different day/night temperature regimes (25/20 °C and 35/30 °C) to investigate the impact of heat stress. Photosynthetic CO2-uptake and electron transport were reduced at the higher temperature, while rates of respiration were greater; suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…The present study would indicate that heat stress has a more pronounced effect on PSII function than drought ( Table 1 ; Figure 2 , Figure 3 and Figure 4 ); consistent with previous field-based observations of the impact of above 40 °C temperatures when combined with drought [ 16 , 33 , 48 ] and leaf gas exchange analysis ( Figure 1 ). The decrease in G s ( Figure 1 ) would reduce heat loss due to transpiration, resulting in higher leaf temperatures, which may contribute to damage to the thylakoid membranes as PSII photochemistry is reduced [ 18 , 49 ]. The OJIP transient suggested that impairment of PSII was more evident in drought stressed plants than in well-watered plants subject to the 35 °C treatment as more energy was dissipated per reaction center ( Figure 2 , Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study would indicate that heat stress has a more pronounced effect on PSII function than drought ( Table 1 ; Figure 2 , Figure 3 and Figure 4 ); consistent with previous field-based observations of the impact of above 40 °C temperatures when combined with drought [ 16 , 33 , 48 ] and leaf gas exchange analysis ( Figure 1 ). The decrease in G s ( Figure 1 ) would reduce heat loss due to transpiration, resulting in higher leaf temperatures, which may contribute to damage to the thylakoid membranes as PSII photochemistry is reduced [ 18 , 49 ]. The OJIP transient suggested that impairment of PSII was more evident in drought stressed plants than in well-watered plants subject to the 35 °C treatment as more energy was dissipated per reaction center ( Figure 2 , Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stomatal regulation is one of the most important adaptation mechanisms to environmental changes such as water deficit [ 10 , 22 , 32 , 62 , 63 ]. However, the limitation of CO 2 availability for photosynthesis due to stomatal closure results in an increase in un-utilized light energy ( Figure 1 ) [ 18 , 24 , 25 , 64 ]. This creates an imbalance between the generation and the utilization of electrons by PSII ( Figure 2 ) and PSI ( Figure 1 ) [ 20 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we observed a reduction in G s H2O in olive during both the heat wave (Figure 1c) and, similar to results obtained in adult olive trees growing in field conditions [53], when exposed to an instantaneous increase in leaf temperature within the leaf cuvette (Figure 5b). Longer-term adaptation to temperature likely affects the response of G s H2O to instantaneous variations in leaf temperature [27,30,31,54]. An increase in leaf to air vapor pressure deficit (VPD) with temperature [50] may have induced stomatal closure in the well-watered olive plants through ABA synthesis [55].…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress may also adversely affect plant water relations by increasing G s H2O [28,29]. However, longer-term stomatal adaptation to growth at higher temperatures (as oppose to instantaneous increases in leaf temperature) may result in no increase in G s H2O [20,27,30,31]. More detailed analysis of the photosynthetic and stomatal responses to temperature of plants from contrasting environments would enable a greater understanding of the likely impacts of heat waves on different vegetation types.…”
Section: Introductionmentioning
confidence: 99%